Pengembangan Sistem Rekomendasi Wisata Kota Medan Berdasarkan Lokasi dan Preferensi Pengguna Menggunakan Algoritma Hybrid Filtering Berbasis Android dan Web - Ghozali, Alexander Valiant; Ratih Adinda Destari (Universitas Methodist Indonesia, 2025)
Medan, the capital of North Sumatra Province, boasts diverse tourism potential, ranging from culinary, historical, and cultural attractions to natural destinations. Unfortunately, many tourists, both local and international, are still unfamiliar with Medan's diverse destinations. This issue is due to limited information that is structured and tailored to the needs and preferences of each user. The solution to addressing the challenges of tourist attraction recommendations in Medan is to design an Android-based application using the hybrid filtering method. A recommendation system is needed to address the challenge of selecting tourist destinations that align with user preferences and can present more personalized and accurate travel options. By considering the characteristics of tourist attractions in Medan and the needs of tourists, the development of an Android-based recommendation system is the right solution to facilitate the search for tourist destinations.